Malignant Mesothelioma of the Tunica Vaginalis Testis-A Malignancy Associated With Asbestos Exposure and Trauma: A Case Report and Literature Review - AAM A. Baqui MD, PhD; Nicholas A. Boire ScM; Tajruba T. Baqui BS; Dhanan J. Etwaru MD (SAGE Publishing, 2019)
In this article, we report an unusual case of a malignant mesothelioma of the testis, presenting as hydrocele. The patient has a known medical history of trauma and occupational exposure to asbestos. The clinical features of this injury are discussed together with its immunohistochemistry. Surgical intervention is discussed due to the nature of this pathology.